Identification of commonly expressed exoproteins and proteolytic cleavage events by proteomic mining of clinically relevant UK isolates of Staphylococcus aureus. Issue 2 (23rd February 2016) - Smith, Debra S.; Siggins, Matthew K.; Gierula, Magdalena; Pichon, Bruno; Turner, Claire E.; Lynskey, Nicola N.; Mosavie, Mia; Kearns, Angela M.; Edwards, Robert J.; Sriskandan, Shiranee
Abstract : The range of exoproteins and core exoproteome of 14 Staphylococcus aureus isolates representing major lineages associated with asymptomatic carriage and clinical disease in the UK was identified by MS proteomics using a combined database incorporating sequences derived from 39 S. aureus genomes. In all, 632 different proteins were identified and, of these, only 52 (8 %) were found in all 14 isolates whereas 144 (23 %) were found in just a single isolate. Comparison of the observed mass of each protein (based on migration by SDS-PAGE) with its predicted mass (based on amino acid sequence) suggested that 95 % of the proteins identified were not subject to any major post-translational modification. Migration of 5 % of the proteins was not as expected: 1 % of the proteins migrated at a mass greater than predicted, while 4 % appeared to have undergone proteolytic cleavage; these included SsaA2, Aur, SspP, Ebh as well as BlaR1, MecR1, FsH, OatA and LtaS. Intriguingly, a truncated SasG was produced by a single CC8 USA300-like strain. The analysis provided evidence of the marked heterogeneity in protein expression by S. aureus in broth, while yielding a core but narrow common exoproteome.